2019
DOI: 10.15244/pjoes/94838
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Contamination Detection in Water and Wastewater Samples Using OD600

Abstract: The effectiveness of disinfection, as well as microbiological composition of water, are assessed by microbiological tests. The analysis usually takes from 24 to 48 hours. During this time the water produced at the water treatment plant has already been fed to the water supply system. In order to reduce the risk of bacteriological contamination, higher concentrations of disinfectants are maintained. Considering the fact that water supply systems use retention tanks with retention times of from 5 to 12 hours, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…After the value of the subgraph centrality of each node is calculated, the subgraph centrality of the super network can be obtained by calculating the average value. In literature [17], the formula for calculating the centrality of the hypernetwork subgraph is…”
Section: Topological Metrics For Hypernetworkmentioning
confidence: 99%
“…After the value of the subgraph centrality of each node is calculated, the subgraph centrality of the super network can be obtained by calculating the average value. In literature [17], the formula for calculating the centrality of the hypernetwork subgraph is…”
Section: Topological Metrics For Hypernetworkmentioning
confidence: 99%
“…We have two speculations. First, the optional density (OD 600 ) was used to measure the concentration of the bacterial solution because that this method is suitable for measuring a large number of cultures, and is more accurate for homogeneous bacterial solutions [42,43] However, these screening strains are aerobic bacteria which can easily live in contact with the air on the surface of the culture medium and whose solutes are not homogeneous (Figure 7), thus the OD 600 value is low. Second, although 1 mL bacterial solution were added to the fresh medium at the beginning of the experiment, the concentration of 1 mL solution (OD 600 ) was not completely consistent from transfer to transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates showed varying rates of growth indicated by differences in turbidity which corresponded to the OD600 values. The degree of turbidity in the broth culture is directly related to the number of microorganisms, studies have shown that cell density is proportional to OD600 according to Domańska et al (2019). Udall et al (2015) reported lower values for growth (0.77-1.80 OD600) by environmental Pseudomonas after 3 days of incubation.…”
Section: Discussionmentioning
confidence: 99%